Electronic structure and characterization of a uranyl di-15-crown-5 complex with an unprecedented sandwich structure. Issue 86 (11th October 2016) - Hu, Shu-Xian; Gibson, John K.; Li, Wan-Lu; Van Stipdonk, Michael J.; Martens, Jonathan; Berden, Giel; Redlich, Britta; Oomens, Jos; Li, Jun
Abstract : A uranyl–di-15-crown-5 complex with a unique slipped sandwich structure was synthesized and characterized by infrared spectroscopy and quantum-chemical methods. Abstract : Understanding of the nature and extent of chemical bonding in uranyl coordination complexes is crucial for the design of new ligands for nuclear waste separation, uranium extraction from seawater, and other applications. We report here the synthesis, infrared spectroscopic characterization, and quantum chemical studies of a molecular uranyl–di-15-crown-5 complex. The structure and bonding of this unique complex featuring a distinctive 6-fold coplanar coordination staggered sandwich structure and an unusual non-perpendicular orientation of the uranyl moiety are evaluated using density functional theory and chemical bonding analyses. The results provide fundamental understanding of the coordination interaction of uranyl with oxygen-donor ligands.